Heterogeneity of tumor immune microenvironment and real-world analysis of immunotherapy efficacy in lung adenosquamous carcinoma - Li, Chao; Zheng, Xiaobin; Li, Pansong; Wang, Huijuan; Hu, Jie; Wu, Lin; Wang, Zhijie; Guo, Hui; Wu, Fang; Zhong, Wenzhao; Zhou, Chengzhi; Chu, Qian; et al. (Frontiers in Immunology, 2022)
Lung adenosquamous carcinoma (ASC) is an uncommon histological subtype. We aimed to characterize the tumor immune microenvironment (TIME) in lung ASC and estimate patient response to immune checkpoint inhibitors (ICIs), which have never been systematically investigated. In cohort I, we collected 30 ASCs from a single center for analysis of TIME characteristics, including immuno-phenotyping, tumor mutation burden (TMB), T cell receptor (TCR) repertoires, tumor-infiltrating lymphocytes (TILs), and immune checkpoint expression. 22 (73.3%) patients were EGFR-positive. The TIME were defined by immune-excluded (60%) and immune-desert phenotype (40%). Strikingly, PD-L1 and PD-1 were predominantly expressed in SCCC versus ACC, where enhanced CD4+ FOXP3+ regulatory T cell and attenuated CD57+ natural killer cell infiltration was present, consistent with a landscape of fewer innate immune cells, more immunosuppressive cells. SCCC had higher TMB, higher TCR clonality, and lower TCR diversity than ACC. In cohort II, the efficacy of ICI-based therapy were estimated using a real-world data of 46 ASCs from 11 centers. Majority of 46 patients were driver genes negative and unknown mutation status, 18 (39%) and 18 (39%), respectively. Overall objective response rate of 28%, median progression-free survival of 6.0 months (95% CI 4.3-7.7), and median overall survival of 24.7 months (95% CI 7.2-42.2) were observed in the ICI-based treatment. This work ascertains suppressive TIME in lung ASC and genetic and immuno-heterogeneity between ACC and SCCC. Lung ASC patients have a moderate response to ICI-based immunotherapy.